Development of Lactococcus lactis Biosensors for Detection of Diacetyl - Hernandez-Valdes, Jhonatan A.; Solopova, Ana; Kuipers, Oscar P. (Frontiers in Microbiology, 2020)
Some secondary metabolites of fermentative bacteria are desired compounds for the food industry. Examples of these compounds are diacetyl and acetaldehyde, which are produced by species of the lactic acid bacteria (LAB) family. Diacetyl is an aromatic compound, giving the buttery flavor associated with dairy products, and acetaldehyde is the compound responsible for the yoghurt flavor and aroma. The quantification of these compounds in food matrices is a laborious task that involves sample preparation and specific analytical methods. The ability of bacteria to naturally sense metabolites has successfully been exploited to develop biosensors that facilitate the identification and quantification of certain metabolites (Mahr and Frunzke, 2016). The presence of a specific metabolite is sensed by the biosensors, and it is subsequently translated into the expression of one or more reporter genes. In this study we aimed to develop fluorescence-based biosensors to detect diacetyl and acetaldehyde. Since the metabolic pathways for production and degradation of these compounds are present in Lactococcus lactis, the sensing mechanisms in this bacterium are expected. Thus, we identified diacetyl and acetaldehyde responsive promoters by performing transcriptome analyses in L. lactis. The characterization of the biosensors showed their response to the presence of these compounds, and a further analysis of the diacetyl-biosensors (its dynamics and orthogonality) was performed. Moreover, we attempted to produce natural diacetyl from producer strains, namely L. lactis subsp. lactis biovar diacetylactis, to benchmark the performance of our biosensors. The diacetyl-biosensors responded linearly to the amounts of diacetyl obtained in the bacterial supernatants, i.e. the increases in GFP expression were proportional to the amounts of diacetyl present in the supernatants of L. lactis subsp. lactis biovar diacetylactis MR3-T7 strain. The biosensors developed in this study may eventually be used to engineer strains or pathways for increased diacetyl and acetaldehyde production, and may facilitate the detection of these metabolites in complex food matrices.